Penggunaan Eudragit L 100 Dalam Formulasi Mikrokapsul Natrium Diklofenak Dengan Teknik Emulsifikasi-Penguapan Pelarut - Rahmadevi, Rahmadevi; Zaini, Erizal; Halim, Auzal (Jurnal Farmasi Andalas, 2013)
It has been research about formulation diclofenac sodium that used Eudragit L100. To prepare, using emulsification-solvent evaporation technique, diclofenac sodium-Eudragit L100 microparticles with modified drug sustained release properties and span 80 is emulgator. Methode research is microcapsules were prepared by solvent evaporation method with ratio diclofenac sodium-Eudragit L100 (1:1,125;1:1,25;1:1,5;1:1,75) and characterized by micromeritics, Scanning Electron Microscopy (SEM), Fourier Transform Infrared Spectroscopy (FTIR), dissolution test using USP apparatus 1 and drug Embadment Efficiency. The result is the microparticle were whitish, irregular, aggregated, and in the size range of 100 â 160 Âµm size. Drug embedment efficiency was 53,7% - 66,3 %. Characterisation studies indicate that there was no chemical interaction between the drug and the polymer in the microparticles. In Dissolution profile ratio diclofenac sodium and Eudragit L100 can slowly drug release were after 450 minute released diclofenac sodium > 50%. Conclusion: Emulsification-solvent evaporation technique is a suitable method for preparing diclofenac sodium-Eudragit L100 multi-unit controlled release drug delivery system.